PENGARUH KOMPRES GEL HANGAT DAN KOMPRES GEL DINGIN UNTUK MENURUNKAN INTENSITAS NYERI DISMENOREA - Maratus Sholikah; Mukhoirotin Mukhoirotin (Indonesian National Nurses Association (INNA) of Central Java, 2023)
The prevalence of dysmenorrhea is still quite high, especially in adolescent girls. If this problem is not addressed immediately, it can affect adolescent achievement both in the academic and non-academic fields. Several studies have shown that warm and cold compresses are effective in reducing dysmenorrhea, while the effectiveness of warm gel compresses and cold gel compresses is not yet clearly known. The purpose of this study was to determine the effect of warm gel compress and cold gel compress on dysmenorrhea. The research design used Quasy Experiment with Two Group Pretest-Postest Design approach, with Simple Random Sampling technique. The sample in this study were 44 respondents who were divided into 2 groups. Warm gel compress and cold gel compress were given on the first day of dysmenorrhea, given for 20 minutes. Pain intensity was measured by Numeric Rating Scale (NRS). Data analysis used Wilcoxon and Mann Whitney tests with p value Ë‚0.05. Dysmenorrhea pain intensity decreased significantly after the intervention of warm gel compress and cold gel compress with a significant value (p) of 0.000 (p <0.05). There is a significant difference between the effect of warm gel compress and cold gel compress on dysmenorrhea with a significant value (p) of 0.011 (p <0.05). Warm gel compress and cold gel compress effectively reduce dysmenorrhea.